Wind in a jar - Farella, John R. (UNM Press Albuquerque, NM, 1993)
This is a book about anthropology & particularly about doing fieldwork among the Navajo. It is ultimately a book about knowing & thinking about people & their experiences, but at its most basic level it is a book of stories about some Navajo people, their families, & some of their experiences. To introduce these stories, the author tells us a good deal about his own experiences in his profession, anthropology. When he is talking about Navajo people we experience their humanity & his, all of it in a remarkably direct prose style. An incredibly powerful book that is also a critique of contemporary American society & Western thought.
64486
Keywords: Anthropology -- Field work; Anthropology -- Philosophy; Navajo Indians